A Honeycomb‐Structured CoF2‐Modified Separator Enabling High‐Performance Lithium−Sulfur Batteries - Wenxin Liu; Yuhang Chu; Jinwei Zhou; Xuanfeng Chen; Yujie Wang; Jinhui Li; Feixiang Wu (Small Science, 2023)
Sulfur cathode materials in lithium–sulfur chemistry suffer from poor electronic conductivity and shuttle of lithium polysulfides during charging and discharging. Serious shuttle effects and the sluggish redox reaction kinetics of polysulfides severely limit the development of lithium–sulfur batteries with high sulfur loading, impeding the practical process of lithium–sulfur batteries. Herein, a honeycomb73x02010;structured CoF2@C is introduced as a functional layer adhered to the separator, achieving rapid lithium‐ion transport, high catalytic activity, and suppressed shuttle effect simultaneously. As a result, the cell with CoF2‐modified separator presents satisfactory cycle stability with a capacity decay of 0.076% per cycle within 300 cycles at 1 C rate with the sulfur loading of 2.0 mg cm−2. A low‐capacity decay of 0.088% per cycle for 200 cycles at 0.2 C is also achieved with sulfur loading of 3.0 mg cm−2. In addition, a high‐capacity retention of 697.5 mA g−1 is achieved with sulfur loading of 4.0 mg cm−2 and the electrolyte volume/sulfur mass (E/S) ratio of 8 μL mg−1.